Medialne obrazy świata z perspektywy retorycznej (na przykładzie recepcji medialnej śmierci i pochówku Czesława Miłosza) - Sobczak, Barbara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The article attempts to contribute to the discussion on the methods used in creating the world in the media, viewed from the rhetorical perspective. Implementations of the rhetorical principle of the adaptation of the utterance to the context and the situation of the audience to which exposition is directed (cf. K. Burke’s idea of identification and the so-called “identification” principle) are followed by both linguistic structuring of the utterance and the following argumentation may effect in the media content messages that are not only different but, frequently, create opposing images of the world. How far they may differ in their message is then shown with the example of the media reception of the death and the burial of Czesław Miłosz manifested in the presentations offered by two daily newspapers: Gazeta Wyborcza and Nasz Dziennik. The excerpted source material shows how the multitude of receivers designed to be reached by different mass media communication channels and diversity in taste and expectations of audiences makes it possible for journalists to create subjective interpretations of the world. Once created and tailored to the context of the audience, they function in parallel pathways and, should a clash between them ensue, the only outcome is that their rhetorical nature gets even more accentuated. With these circumstances given, what we experience then is a situation when different truths collide, while each of them surfaces within a given context of human conversation and each is validated by its respective audience to be reached and goals to be attained.